(untitled) (Research, Society and Development, 2022)
This study aims to assess the use of medicinal Cannabis for donor treatment, analyzing topics such as better donor and collateral effects. It is a systematic review carried out through the SciELO, LILACS and Medline/PubMed databases with observational studies published in the last 5 years. Not total, forams found 13,910 items, after applying the criteria of inclusion and exclusion subtract 18 studies to compare based on data. Forams analyzed 7,389 patients, with a predominance of the female sex (n=3,623). Chronic pain was the most mentioned in the studies (n=1,492 cases), followed by neuropathic pain (n=870 cases) and pain after injury/trauma (n=794 cases). In 10 studies, with a sample of 4,611 patients, 3,579 (77.62%) reported an improvement in their sleep level after starting Cannabis use. Other benefits of this treatment were improved sleep, reduced use of opioids, and improved quality of life. For chronic refractory or low response to conventional treatment, the use of Cannabis is a good option, since it is capable of relieving pain, as well as its associated symptoms, or that it improves the quality of life of the patient and also reduces the opioid use.